FAKTOR - FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI SEMANGKA NON BIJI DI DESA SUNGAI PAGAR KECAMATAN KAMPAR KIRI HILIR KABUPATEN KAMPAR - Novi Apriyanti; Sisca Vaulina (DINAMIKA PERTANIAN, 2023)
Non-seed farming is one of the farmers' livelihoods in Sungai Pagar Village, Kampar Kiri Hilir District, Kampar region. Farmers' income can be increased through utilization inputs effectively and efficiently. This study aims to analyze: Characteristics of farmers and non-seed watermelon farming profiles, Use of non-seed watermelon cultivation technology 3). Cost of farming, production, income, and farm efficiency, factors that affect the income of non-seed watertermelon farming. The study was conducted by survey method and location was chosen purposively in Sungai Pagar Village. Sample were taken by simple random sampling on 45 farmers. Data analysis used are qualitative and quantitative descriptive, and multiple regression. Based on the results the average characteristics of non-seed watermelon farmers were highest of 15 people age, level of education of 12 years (25 people), gender majority of men, experience of farming 5-9 years (30 people), and the number of family dependents-4 people (23 people). Non-seed watermelon farming uses its capital, the status of ownership of leased land, with an area of 2.0 ha-6.0 ha, male workers total of 2.71 HKP. The cost of farming is IDR 8,381,122 kg/MT, gross income IDR 67,444,444 kg/MT, net income IDR 71,266,667 kg/MT, efficiency value of 1,05. Dominant factors affecting non-seed watermelon farm income were production, labor costs outside the family, production, selling prices, and seed costs that experience a significant effect on non-seed watermelon farm income. While the level of education, farming experience, and age insignificantly affect watermelon farm income.